Pola lingkaran pertumbuhan pada otolith ikan gadih (Tor tambroides) - Isma Mulyani; Windarti; Melisa Oktaviani (JURNAL MINA SAINS, 2026)
Tor tambroides (Cyprinidae), or gadih fish, was an endemic fish that inhabited the upstream of the Kampar Kanan River. The population and habitat of this fish have been reduced. As the fish's life quality is reflected in the growth pattern in the otolith, the cause of this fish's decline may be investigated through its growth ring pattern in the otolith. A study aimed to comprehend the pattern of otolith growth rings was conducted from August to October 2023. The fish were gathered from fishermen who caught them in the river area that crosses Bandur Picak Village. A total of 31 fish were captured during the study. The otoliths were then removed, processed, and investigated under a binocular microscope. Results showed that the size of fish captured ranged from 77-1521 g BW and 194-505 mm TL, while the otolith size was 2-5 mm in length and 0,0028-0,0148 g in weight. In all fishes captured, the number of dark rings in the otolith was only 1-2 rings, and the distance between the nucleus and the first dark ring ranged from 0.5 to 1 mm.  There was no special pattern at those distances, indicating that the dark growth rings were not caused by periodic incidents, but were formed individually. Based on the number and the pattern of the otolith’s growth rings, it can be concluded that the life quality of the fish was relatively good and that it rarely faced problems that hamper their growth, as reflected in the otolith growth ring pattern.